2010
DOI: 10.1186/1471-2407-10-318
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-125a-3p and hsa-miR-125a-5p are downregulated in non-small cell lung cancer and have inverse effects on invasion and migration of lung cancer cells

Abstract: BackgroundTwo mature microRNAs (miRNAs), hsa-miR-125a-3p and hsa-miR-125a-5p (collectively referred to as hsa-miR-125a-3p/5p), are derived from 3' and 5' ends of pre-miR-125a, respectively. Although impaired regulation of hsa-miR-125a-5p has been observed in some tumors, the role of this miRNA in invasion and metastasis remains unclear, and few studies have examined the function of hsa-miR-125a-3p. In order to characterize the functions of hsa-miR-125a-3p/5p in invasion and metastasis of non-small cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
182
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(187 citation statements)
references
References 45 publications
5
182
0
Order By: Relevance
“…The miR-125 family has 2 mature isoforms: miR-125a and miR-125b (encoded by miR125b-1 and miR-125b-2). Deregulated expression of miR-125 family members in various cancers has been reported [53][54][55] . Tili et al [56] has earlier demonstrated that miR125b is of importance for the innate immune response, as lipopolysaccharide (LPS) stimulation of a murine macrophage cell line caused suppressed miR-125b levels.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-125 family has 2 mature isoforms: miR-125a and miR-125b (encoded by miR125b-1 and miR-125b-2). Deregulated expression of miR-125 family members in various cancers has been reported [53][54][55] . Tili et al [56] has earlier demonstrated that miR125b is of importance for the innate immune response, as lipopolysaccharide (LPS) stimulation of a murine macrophage cell line caused suppressed miR-125b levels.…”
Section: Discussionmentioning
confidence: 99%
“…miR-125a-5p is located at 19q13.41, and its downregulated expression in non-small cell lung cancer (NSCLC) was first observed in 2006 (28). A number of studies have demonstrated that the role of miR-125a-5p as a tumor-inhibiting factor in several types of tumors, including breast cancer, NSCLC and ovarian cancer (29)(30)(31). Additionally, Tong et al (32) have demonstrated that miR-125a-5p miRNA was downregulated in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the miR-12 target PTEN, which is a negative regulator of the PKB-AKT pathway, is involved in NSCLC cell line invasion (12)(13)(14). A previous study demonstrated that miR-125a-3p and -5p are downregulated in primary NSCLC tumors, but that they serve an opposing role in lymph node metastases (15). miR-328 and miR-206 have also been associated with NSCLC brain metastasis (16,17).…”
Section: Introductionmentioning
confidence: 99%